Take my word for it: How professional vocabularies foster organizing. (6th January 2014) - Loewenstein, Jeffrey
Abstract: Professional vocabularies are sources of categories that non-professionals borrow and use. Accordingly, professions play a key role in divisions of linguistic labor, generating and distributing, but maintaining control over, words that other use to guide their thinking and behavior. Collectively, organizations and fields coordinate in part through integrating words borrowed from multiple professional vocabularies, simultaneously broadening common ground across their members and assigning jurisdictions to specialized members. Thus, professional vocabularies are not only barriers but also largely unnoticed facilitators of organizing.